2016
DOI: 10.1148/radiol.2015150796
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Cancer Detected at Breast MR Imaging and Not at Mammography: Important or Not?

Abstract: ).q RSNA, 2015 Purpose:To review the magnetic resonance (MR) imaging and pathologic features of multicentric cancer detected only at MR imaging and to evaluate its potential biologic value. Materials and Methods:This retrospective study was institutional review board approved and HIPAA compliant; informed consent was waived. Results:Known index cancers were more likely to be invasive than MR imaging-detected multicentric cancers (88% vs 76%, P = .023). Ductal carcinoma in situ (21 of 87 lesions [24%]; 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
4
38
2
Order By: Relevance
“…Similar to other recently published studies, we found that the majority of MRI‐detected, mammographically occult CBC were diagnosed as stage 0 or stage IA, with DCIS representing over a third of all CBC. This may have significant clinical implications in the modern era of DCIS management.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other recently published studies, we found that the majority of MRI‐detected, mammographically occult CBC were diagnosed as stage 0 or stage IA, with DCIS representing over a third of all CBC. This may have significant clinical implications in the modern era of DCIS management.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our study to some degree refutes the notion that MRIs are most effective as an adjunct to staging for women with dense or extremely dense breasts; we found that a third of CBC was detected in patients with breasts mammographically described as fatty or with scattered fibroglandular densities, higher than reported by Iacconi et al 25 who published that MRI detected mammographically occult ipsilateral multicentric disease more frequently in patients with heterogeneously or extremely dense breasts. 25 We acknowledge limitations to this study.…”
Section: Discussionsupporting
confidence: 59%
“…9,10 MRI detection rates of otherwise occult contralateral breast cancer range from 3.1% to 5.5%, 10,11 while detection rates for occult multicentric disease have been reported to be as high as 3.6%. 12 In a previous publication from our group, which included neoadjuvant patients, the rate of occult cancer detection was 7.5%. 13 In the current study, we found detection rates of additional lesions by MRI that were similar to those of previous studies, resulting in rates of detection of 6.2% for occult multifocal cancers, 1.9% for occult multicentric cancers, and 3.1% for occult contralateral cancers.…”
Section: Discussionmentioning
confidence: 86%
“…Recent meta‐analyses cite MRI detection rates of additional disease ranging from 16% to 20% 9,10 . MRI detection rates of otherwise occult contralateral breast cancer range from 3.1% to 5.5%, 10,11 while detection rates for occult multicentric disease have been reported to be as high as 3.6% 12 . In a previous publication from our group, which included neoadjuvant patients, the rate of occult cancer detection was 7.5% 13 .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, breast MRI most accurately depicts the extent of breast cancer (4)(5)(6). Although the clinical relevance of additional lesions is still controversial, preoperative MRI identifies more synchronous, ipsilateral or contralateral breast cancers than mammography and ultrasound (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%